A2MIPARI (Aksi Anak Membaca Iqra’ Pagi Hari); Pembelajaran Al-Qur’an pada Pendidikan Anak Usia Dini “Ash-Shiby” - Akbar, Eliyyil (Al-Athfal: Jurnal Pendidikan Anak, 2017)
The children is a sensitive time which is something that he obtained is easily drenched with how to learn while playing. The habit of children playing can be made reference to become the habit of learning, so that the same used to play and learn. The habit of learning to read the Qur'an is done by repeatedly as consequence of Early Child Education "Ash-Shiby" that learning the Qur'an done in the morning before the start of formal activities done because the morning is very effective in giving time and the spirit of the enthusiasm of children in exercising. This paper describes the implementation of A2MIPARI (Action Children Read Iqra' Morning); learning the Qur'an in the Early Child Education "Ash-Shiby" and the result of A2MIPARI (Action Children Read Iqra' Morning). The implementation of A2MIPARI not contained in a lesson plan and accommodate the moral development of religion and the Bible. The results from A2MIPARI is enthusiastic and motivated so that the progress of reading children always increased in every week. The actualisation can serve as a reference point in the teach the Qur'an making kebermaknaan life that reflected from the contents of the Qur'an.